2009
DOI: 10.2174/1874300500802010050
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Misuse Prevalence and Associations with Post-Operative Complications in US Surgical Patients: A Review

Abstract: Abstract:We conducted a standardized review of research on the prevalence of alcohol use or misuse (including alcohol use disorders), and the association of alcohol use or misuse with post-operative surgical complications among US patients. Twenty seven studies that included a preoperative measure of alcohol use or misuse and included at least 50 US surgical patients were identified using a standardized search strategy (1950( -April 2007. Twenty-two of the studies reported prevalence of alcohol use or misuse, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Each year 14% of Americans meet criteria for an alcohol use disorder and 13% smoke cigarettes 1,2 . In surgical populations, the prevalence of these behaviors is higher, with as many as 1 in 4 surgical patients smoking and/or drinking alcohol at risky levels 3,4 . In fact, smoking and risky alcohol use (defined as consuming >2 drinks per day) before surgery are 2 of the most common risk factors for poor outcomes after surgery 5 .…”
mentioning
confidence: 99%
“…Each year 14% of Americans meet criteria for an alcohol use disorder and 13% smoke cigarettes 1,2 . In surgical populations, the prevalence of these behaviors is higher, with as many as 1 in 4 surgical patients smoking and/or drinking alcohol at risky levels 3,4 . In fact, smoking and risky alcohol use (defined as consuming >2 drinks per day) before surgery are 2 of the most common risk factors for poor outcomes after surgery 5 .…”
mentioning
confidence: 99%
“…head and neck tumour surgeries). 103 This suggests a number of possibilities: alcohol consumption levels may be much lower in certain surgical populations, those drinking at risky levels may be less likely to participate in intervention trials or alcohol consumption may be under-reported by trial participants. Fernandez et al 99 recommend adopting clear, precise definitions of risky drinking and using unbiased screening to detect those drinking at risky levels.…”
Section: Behavioural Interventions In the Preoperative Periodmentioning
confidence: 99%
“…Qualitative evidence 92 has identified time and burden of new processes as key barriers to the implementation of alcohol screening and BI, and findings from alcohol screening studies conducted in PA have reported that the majority of patients drink at 'safe' or 'sensible' drinking levels. 62,103 Therefore, it is appropriate to use a short initial screen (AUDIT-C) to identify potentially eligible patients, with the longer full AUDIT being used to inform intervention delivery and, potentially, the tailoring of intervention content.…”
Section: Screening Tool Selectionmentioning
confidence: 99%
“…A growing body of research indicates that risky drinking prior to surgery can have a detrimental impact on postoperative recovery [19,[21][22][23][24][25][26][27]. Rates of risky alcohol use prior to elective surgeries range from 30.0% to 88.5% among otolaryngology surgeries, from 29% to 33% among vascular and thoracic surgeries and from 7.7% to 28.0% among other types of surgery [28]. The research linking risky drinking and postoperative problems is robust.…”
Section: Alcohol Use and Postoperative Morbidity And Mortalitymentioning
confidence: 99%